Exploring the Depths: The Significance of Analysis in Unveiling the Other Side of Perception - Diyah Nurhayati; Windy Esti Andari; Tria Aprilia (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the role of analysis in revealing other sides of perception in the context of works of art, especially in music. With a focus on the theme "other side of the eye", this research explores how analysis allows a deep understanding of the layers of meaning hidden behind the work of art. By involving an interdisciplinary approach and relevant case examples, this study strengthens the importance of analysis as an essential tool in unraveling the complexity of works of art.